Do not disturb the family: roles of colony size and human disturbance in the genetic structure of lesser kestrel. (13th November 2014) - Di Maggio, R.; Mengoni, C.; Mucci, N.; Campobello, D.; Randi, E.; Sarà, M.
Abstract Dispersal and philopatry are fundamental processes influencing the genetic structure and persistence of populations, and might be affected by isolation and habitat perturbation. Habitat degradation induced by human activities could have detrimental consequences on the genetic structure of populations. Therefore, it is crucial to understand the role of human impact in promoting or disrupting the genetic structure. Here, we conducted a genetic analysis using 12 polymorphic microsatellite markers of 70 lesser kestrels Falco naumanni from 10 breeding colonies of two subpopulations in Sicily (southern Italy). Genetic differentiation between the two subpopulations was negligible, and linear distances played no role in the level of genetic relatedness recorded in the two sites. Linear distances between nests also resulted in no effects on the relatedness recorded within and between colonies in the largest subpopulation. Clusters of more‐versus less‐related individuals resulted when the two‐dimensional positions of colonies (i.e., latitude and longitude) were tested as predictors of genetic proximity instead of linear distances. Specifically, analyses of colony features showed colony size and human disturbance as factors negatively affecting the relatedness among chicks from different nests. Regardless of colony size, less‐related individuals were born in colonies located in the core of the agricultural plain, where we quantified a higher level of human disturbance. In contrast, more related individuals were in colonies located in the marginal, less disturbed, agricultural area. Given the high philopatry of this species, our results are consistent with disruption of colony fidelity related to intensification of agricultural practices. We discuss the possible implications of long‐term effects of genetic variability in small and disturbed colonies on fitness and population viability.